2015
DOI: 10.3390/cells4020112
|View full text |Cite
|
Sign up to set email alerts
|

Signaling during Kidney Development

Abstract: The kidney plays an essential role during excretion of metabolic waste products, maintenance of key homeostasis components such as ion concentrations and hormone levels. It influences the blood pressure, composition and volume. The kidney tubule system is composed of two distinct cell populations: the nephrons forming the filtering units and the collecting duct system derived from the ureteric bud. Nephrons are composed of glomeruli that filter the blood to the Bowman’s capsule and tubular structures that reab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 121 publications
1
65
0
Order By: Relevance
“…Important signalling molecules such as several Wnts and Notch2 were found to be associated with EVs (summarized in [4]). Gradilla and co-workers showed that the transport of the morphogen hedgehog (Hh) is important for proper spatially restricted signalling during development [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Important signalling molecules such as several Wnts and Notch2 were found to be associated with EVs (summarized in [4]). Gradilla and co-workers showed that the transport of the morphogen hedgehog (Hh) is important for proper spatially restricted signalling during development [5].…”
Section: Introductionmentioning
confidence: 99%
“…Besides the survival signals, the UB also secretes signals that induce the MM to undergo nephrogenesis, such as the Wnt ligands [12–14], resulting in the development of the key functional kidney units – the nephrons [4]. While the UB is a natural MM nephrogenesis inducer, it can be removed and replaced by chemical activation of the Wnt pathway via the GSK-3 inhibitor (BIO) [15] in the process of renal organoid formation [16].…”
Section: Introductionmentioning
confidence: 99%
“…54 EMT, for instance, has been described in the kidney, liver, and pancreas of mammals during early embryonic development. [55][56][57][58] Similar pathways are present in carcinomas of various organs where L1CAM converts epithelial cells into a migrating phenotype via the stimulation of the beta-catenin pathway and inhibition of adherens junction formation. 59 Moreover, abolition of the cell-cell contacts is triggered by a cleavage Editor's Highlight of the L1CAM ectodomain via the metalloproteinases ADAM 10 and 17.…”
Section: Discussionmentioning
confidence: 96%
“…As a result, epithelial stem cells in the tip of a CD ampulla meet GDNF + /Six2 + /CITED1 + mesenchymal cells [51, 52]. At the same time, a reciprocal exchange of morphogens within the niche takes place [37, 38]. When the signaling for the process of induction is successful, a few mesenchymal cells separate, aggregate, and perform a mesenchyme-to-epithelial transition (MET) to develop into a renal vesicle at the lateral aspect of the related CD ampulla [63].…”
Section: Fine Positioning Of Stem Cellsmentioning
confidence: 99%
“…Initiated by branching morphogenesis, it shows a radial and, at the same time, fan-like extension [32-36]. On the other hand, intact development of nephrons principally presupposes successive interactions between branches of the ureteric bud and facing mesenchymal stem cells [37, 38]. …”
Section: Eccentric Position Of the Nephrogenic Zonementioning
confidence: 99%